Preservation of the Selwasa Language in Batu Putih Village - Fenanlabir, Ursula Margarita; da costa, Romilda Arivina; Pesiwarissa, Leonora Farilyn (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The preservation of the Selwasa language in Batu Putih Village, Wermaktian District, Tanimbar Islands Regency. This study seeks to elucidate the social phenomena of language maintenance in Batu Putih Village, Wermaktian District, Tanimbar Islands Regency. This research employs a qualitative methodology centred on language maintenance, assessed through language usage in the domains of family, neighbours, employment, religion, customs, and education. The methods employed for data collection included observation, interviews, questionnaires, and documentation. The research findings indicate that in Batu Putih Village, the predominant usage of the Selwasa language is evident in the domains of family and customs, with additional support from the domain of neighbours. Ambon Malay exhibits the lowest prevalence relative to the Selwasa language across the three domains. According to the speakers' ages, GL speakers constitute the biggest percentage, followed by GT, with GM having the lowest percentage. Conversely, farmers exhibit the largest percentage of Selwasa language usage compared to other professions. Consequently, it can be asserted that the Selwasa language remains well-preserved in Batu Putih Village.